Combined training in addition to cortisol reduction can improve the mental health of girls with precocious puberty and obesity - Heidarianpour, Ali; Shokri, Elnaz; Sadeghian, Efat; Cheraghi, Fatemeh; Razavi, Zahra (Frontiers in Pediatrics, 2023)
Background Obesity and central precocious puberty (CPP) are associated with increased anxiety, depression, and anger in girls. The contribution of exercise as an efﬁcacious component in decreasing anxiety, depression, and anger has been increasingly recognized. Objectives This study aims to evaluate the effects of combined training on cortisol, anxiety, depression, and anger in overweight and obese girls with CPP. Methods The study involved 30 girls aged 7–9 years diagnosed with CPP (undergoing triptorelin treatment) and dealing with obesity. In addition, these girls scored higher than the cut-off line for anxiety, depression, and anger. The participants were divided into two groups, with 15 individuals in each group. The exercise group engaged in 60 min of combined aerobic and resistance training three times per week for a duration of 12 weeks. On the other hand, the control group did not receive any training. Throughout the study, the serum cortisol levels were measured in both groups. Anxiety, anger, and depression questionnaires were also completed at three different stages, namely, baseline, 12 weeks, and 16 weeks (after a 4-week period of detraining). Results In the exercise group, there was a significant decrease (P < 0.05) in cortisol serum levels and anxiety, depression, and anger scores. These changes were observed consistently during detraining (P > 0.05). However, in the control group, only the depression score significantly decreased (P < 0.05). Conclusions Based on the results, it can be concluded that combined training is a method to improve the mental health of CPP girls. Clinical Trial Registration https://en.irct.ir/trial/61990, identifier IRCT20170411033378N10.